Africa-centred knowledges : crossing fields and worlds - Cooper, Brenda; Morrell, Robert; Soudien, Crain (James Currey, 2014)
Proposes a dynamic new approach to the production of knowledge on Africa, one that is global, multiple and heterogeneous, elucidating this through both discursive theoretical chapters and case histories.